Description Of Diarrhea Treatment In Children with â€Oralitâ€ Corner At Puskemas Togo-Togo - Safrianty, Eka; Hafid, Muhammad Iskandar (Politeknik Kesehatan Makassar, 2021)
Diarrhea is a change in stool consistency of fases and an increased frequency during bowel movements. Someone is said to have diarrhea if the stool is loose or runny, if you defecate in a day three or more times within 24 hours. Diarrhea can cause morbidity and mortality rates. So with this, the Puskesmas will carry out the initial handling of diarrhea in children by providing an Oralit Corner in the Puskesmas waiting room. Improper handling and treatment of diarrhea can lead to serious dehydration problems. The provision of an Oralit corner is one of the efforts made by the Puskesmas TogoTogo (Public Health Center). With the Oralit corner, it is very useful to prevent dehydration in children who suffer from diarrhea thus it is necessary to continuously monitor the storage, distribution and supply of Oralit.